Gandhi’s Militant Nonviolence in the Light of Girard’s Mimetic Anthropology - Palaver, Wolfgang (Religions, 2021)
Nuclear rivalry, as well as terrorism and the war against terror, exemplify the dangerous escalation of violence that is threatening our world. Gandhi’s militant nonviolence offers a possible alternative that avoids a complacent indifference toward injustice as well as the imitation of violence that leads to its escalation. The French-American cultural anthropologist René Girard discovered mimetic rivalries as one of the main roots of human conflicts, and also highlighted the contagious nature of violence. This article shows that Gandhi shares these basic insights of Girard’s anthropology, which increases the plausibility of his plea for nonviolence. Reading Gandhi with Girard also complements Girard’s mimetic theory by offering an active practice of nonviolence as a response to violent threats, and by broadening the scope of its religious outreach. Gandhi’s reading of the Sermon on Mount not only renounces violence and retaliation like Girard but also underlines the need to actively break with evil. Both Gandhi and Girard also address the religious preconditions of nonviolent action by underlining the need to prefer godly over worldly pursuits, and to overcome the fear of death by God’s grace. This congruence shows that Girard’s anthropology is valid beyond its usual affinity with Judaism and Christianity.